090 Clinical trials in amyotrophic lateral sclerosis: a systematic review. Issue 6 (27th May 2022) - Wong, Charis; Dakin, Rachel; Chataway, Jeremy; Swingler, Robert; Weir, Christopher; Stallard, Nigel; Parmar, Mahesh; Macleod, Malcolm; Pal, Suvankar; Chandran, Siddharthan
Abstract : Background: Amyotrophic lateral sclerosis (ALS) is a rapidly fatal neurodegenerative disease. Despite decades of clinical trials, there remains a pressing unmet need for effective treatments. We reviewed past and present ALS clinical trials to understand the methodological challenges in trial design and delivery. Methods: Trial registry databases including clinicaltrials. gov, International Clinical Trials Registry Platform, European Union Clinical Trials Register, and PubMed were systematically searched to identify Phase II, Phase II/III and Phase III Clinical Trials of Investigational Medicinal Products (CTIMPs) assessing potential disease modifying treatments in ALS. Trials registered, completed or published during 2008–2019 were included. Results: 125 CTIMPs, evaluating 76 drugs, involving 15647 people with ALS (pwALS) were reviewed. Ten drugs were tested in three or more trials. Trials employed predominantly traditional two-arm designs; only 12 used novel designs. Median number of participants was 86. 40% of trials had an attrition rate ≥ 20%. There was a wide variation of primary outcome measures and primary endpoints used. Conclusion: Historically, limited participation of pwALS in trials, resources and outcome measures hindered definitive and timely evaluation of drugs in two-arm trials. We propose that future trials will need to be more flexible, scalable and acceptable to all stakeholders. charis.wong@ed.ac.uk